Evaluation of the Suitability of the Implementation of the Project in Contracts Quality Plan - Zulkarnain, Isnaini; Noor, Rusandi; ., Pitoyo (International Journal of Engineering and Technology, 2019)
This paper aims to evaluated the quality control of project implementation and the determining factors conformity of the implementation of the contract quality plan on the project. Here we discuss road projects in East Kalimantan because according to the central government infrastructure instruction that must be prioritized is road construction. Because there is still a lack of service on road infrastructure in East Kalimantan. Statistical method is Importance Performance Analysis (IPA), through validation and reliability testing variable item through data collection of respondents in the form of questionnaires. Factors that cause a striking difference between contract execution plans with the quality of the road project in East Kalimantan. Have weaknesses in operational variables (X 1) indicator more obvious scheduling system and planned (X 1.6) it has a score of 0.55 and human resource variables (X 3) on the recruitment and training of the indicator (X 3.12) has a score of 0.56. This paper provides references to insight and understanding about method of evaluating nonconformity, corrective and preventive actions in implementing contract quality plans in project implementation.Â